Blacktip reef sharks, Carcharhinus melanopterus, have high genetic structure and varying demographic histories in their Indo‐Pacific range. Issue 21 (13th October 2014) - Vignaud, Thomas M.; Mourier, Johann; Maynard, Jeffrey A.; Leblois, Raphael; Spaet, Julia; Clua, Eric; Neglia, Valentina; Planes, Serge
Abstract For free‐swimming marine species like sharks, only population genetics and demographic history analyses can be used to assess population health/status as baseline population numbers are usually unknown. We investigated the population genetics of blacktip reef sharks, Carcharhinus melanopterus; one of the most abundant reef‐associated sharks and the apex predator of many shallow water reefs of the Indian and Pacific Oceans. Our sampling includes 4 widely separated locations in the Indo‐Pacific and 11 islands in French Polynesia with different levels of coastal development. Four‐teen microsatellite loci were analysed for samples from all locations and two mitochondrial DNA fragments, the control region and cytochrome b, were examined for 10 locations. For microsatellites, genetic diversity is higher for the locations in the large open systems of the Red Sea and Australia than for the fragmented habitat of the smaller islands of French Polynesia. Strong significant structure was found for distant locations with FST values as high as 0.3, and a smaller but still significant structure is found within French Polynesia. Both mitochondrial genes show only a few mutations across the sequences with a dominant shared haplotype in French Polynesia and New Caledonia suggesting a common lineage different to that of East Australia. Demographic history analyses indicate population expansions in the Red Sea and Australia that may coincide with sea level changes after climatic events. Expansions and flat signals are indicated for French Polynesia as well as a significant recent bottleneck for Moorea, the most human‐impacted lagoon of the locations in French Polynesia.